Effects of Ginkgo Biloba Extract on Periodontal Pathogens and Its Clinical Efficacy as Adjuvant Treatment - 程茜 高伟民 曹彬 刘颖梅 林梅 张良琼 王一松 王左敏 (Chinese journal of integrative medicine, 2014)
Objective：To determine the effects of Ginkgo biloba extract（EGB） on major periodontal pathogens in subgingival plaque.Methods：Sixty patients with moderate to severe periodontitis were selected and randomly assigned to 3 groups：EGB group,a positive（periocline） and a negative control groups.Subgingival plaque samples were collected before treatment and 1 week,2 months and 4 months after treatment.The detection rates of 4 major periodontal pathogens—Treponema denticola（Td）,Tannerella forsythus（Tf）,Prevotella intermedia（Pi）,and Porphyromonas gingivalis（Pg）—were detected by polymerase chain reaction（PCR）.Clinical indicators were examined before treatment,3 and 6 months after treatment.Results：EGB significantly decreased the detection rate of all the 4 pathogens 1 week after treatment,and then gradually increased at 2 and 4 months.EGB＇s inhibition effect was better than or comparable to periocline,except for Pg in short-term.The difference of plaque index（PLI） and bleeding index（Bl） was not statistically significant among the groups,while for probing depth（PD） and attachment loss（AL）,the difference was statistically significant between the EGB group and negative control group at 3 and 6 months after treatment.Conclusion：EGB significantly inhibited major periodontal pathogens and can be used as an adjuvant for periodontitis treatment.